The metabolic function of cyclin D3–CDK6 kinase in cancer cell survival - Wang, Haizhen; Nicolay, Brandon N.; Chick, Joel M.; Gao, Xueliang; Geng, Yan; Ren, Hong; Gao, Hui; Yang, Guizhi; Williams, Juliet A.; Suski, Jan M.; Keibler, Mark A.; Sicinska, Ewa; et al. (Nature (London), 2017)
The cyclin D3–CDK6 kinase complex, which is overactive in some cancers, inhibits two key glycolysis enzymes and thereby enhances the levels of antioxidants in cells, promoting tumour cell survival. Cancer cell survival by cyclin D3–CDK6 metabolism Cyclin–CDK complexes are commonly amplified in cancer and promote cell cycle progression. Inhibitors for CDK4/6 are being tested in clinical trials and are thought to work in patients that retain expression of the CDK substrate RB1. Here, the authors describe an additional pro-survival role of one cyclin–CDK complex, D3–CDK6, which controls cellular metabolism. When hyperactivated in cancer cells, the complex phosphorylates and inactivates two glycolysis enzymes. This redirects glycolytic intermediates to the pentose phosphate and serine pathways, providing enhanced antioxidant capacity. CDK4/6 inhibitors can induce apoptosis by increasing the oxidative stress in tumour cells expressing high levels of D3–CDK6 complexes. The findings suggest that, in addition to RB1, markers such as levels of D3–CDK6 complexes could be useful for identifying patients likely to respond to CDK4/6 inhibitors. D-type cyclins (D1, D2 and D3) and their associated cyclin-dependent kinases (CDK4 and CDK6) are components of the core cell cycle machinery that drives cell proliferation 1 , 2 . Inhibitors of CDK4 and CDK6 are currently being tested in clinical trials for patients with several cancer types, with promising results 2 . Here, using human cancer cells and patient-derived xenografts in mice, we show that the cyclin D3–CDK6 kinase phosphorylates and inhibits the catalytic activity of two key enzymes in the glycolytic pathway, 6-phosphofructokinase and pyruvate kinase M2. This re-directs the glycolytic intermediates into the pentose phosphate (PPP) and serine pathways. Inhibition of cyclin D3–CDK6 in tumour cells reduces flow through the PPP and serine pathways, thereby depleting the antioxidants NADPH and glutathione. This, in turn, increases the levels of reactive oxygen species and causes apoptosis of tumour cells. The pro-survival function of cyclin D-associated kinase operates in tumours expressing high levels of cyclin D3–CDK6 complexes. We propose that measuring the levels of cyclin D3–CDK6 in human cancers might help to identify tumour subsets that undergo cell death and tumour regression upon inhibition of CDK4 and CDK6. Cyclin D3–CDK6, through its ability to link cell cycle and cell metabolism, represents a particularly powerful oncoprotein that affects cancer cells at several levels, and this property can be exploited for anti-cancer therapy.